(untitled) (Mustansiria Dental Journal, 2018)
Background:The purpose of this study was to evaluate the effect of different concentrations of water cinnamon extract on growth of mutans streptococci, in comparison to chlorhexidine gluconate (0.2%), Zac [0.12% chlorhexidine with 0.05% sodium fluoride (Maleh Chemical products, Syria)] and deionized water in vitro and viability counts of mutans streptococci among a number of volunteers. Material and Methods:Stimulated saliva was collected from six healthy looking students aged (22-24) from which mutans streptococci were isolated. Sensitivities of mutans streptococci according to Agar Well Technique showed that mutans streptococci were more sensitive to chlorhexidine and Zac compared to water cinnamon extract. The effect of these agents on the viability counts of mutans streptococci in comparison to the control in vitro were studied, a significant reduction in the counts of bacteria at concentrations 20% of water cinnamon extract was illustrated (P<0.05), at higher concentrations water cinnamon extract showed a highly significant reduction in the counts of bacteria(P<0.001), concerning chlorhexidine, and Zac there was a highly significant reduction in the counts of bacteria in comparison to the control after 24 hour(P<0.001). The study involved one in vivo experiment to test the effect of water cinnamon extract (20%) against salivary mutans streptococci in comparison to 0.2% chlorhexidine, Zac and deionized water. Stimulated saliva was collected from 20 subjects (22-25), they were divided into four groups, each group rinse once with either chlorhexidine, Zac, cinnamon extract or deionized water. A non significant difference was found between cinnamon and chlorhexidine compared to deionized water in the counts of bacteria after thirty minute. There was a highly significant difference between Zac and deionized water, rinsing with Zac resulted in a highly significant reduction in the count of bacteria within this time followed by chlorhexidine which was not significantly difference from cinnamon, deionized water showed a slight reduction in the counts of bacteria. The same result was shown after one hour, within this time chlorhexidine resulted in a highly significant reduction in the counts of bacteria compared to deionized water. After two hours of rinsing there was no significant difference between cinnamon and deionized water in the counts of bacteria. Conclusion:Cinnamon would be a useful compound for development of antibacterial agents against mutans streptococci although its effectiveness was less than chlorhexidine but it may has potential for use in mouthwash for preventing dental caries.